3D Airway changes using CBCT in patients following mandibular setback surgery ± maxillary advancement. (10th May 2019) - Havron, Andrew G.; Aronovich, Sharon; Shelgikar, Anita V.; Kim, H. Ludia; Conley, R. Scott
Structured Abstract: Introduction: The aim of this study was to determine the 3D airway changes that occur following mandibular setback surgery alone vs bimaxillary surgery in patients with similar skeletal start forms. Setting and Sample Population: The University of Michigan School of Dentistry and Medical Center. A total of 85 patients undergoing mandibular setback with or without simultaneous maxillary advancement. Materials and Methods: A retrospective evaluation of pre‐ and post‐surgical CBCT scans for patients undergoing mandibular setback surgery alone (14) vs bimaxillary surgery (71) was performed. Cross‐sectional evaluation at standardized locations, minimum cross section and volumetric analysis were performed (Dolphin Imaging & Management Solutions). Results: Patients who underwent mandibular setback surgery alone showed a statistically significant average increase of 47.5 mm 2 in minimum axial area. Patients who underwent bimaxillary surgery showed a statistically significant increase in airway volume, minimum axial area, location of minimum axial area, and axial area at the retropalatal and retroglossal regions. Conclusions: The results demonstrate that the mandible can be setback safely without decreasing airway dimensions. In borderline OSA patients, bimaxillary surgery remains the preferred approach due to the larger airway increases observed. Long‐term follow‐up with polysomnography must be conducted to determine the full functional implications of both procedures.